2021
DOI: 10.1038/s41586-021-03358-w
|View full text |Cite|
|
Sign up to set email alerts
|

REV-ERB in GABAergic neurons controls diurnal hepatic insulin sensitivity

Abstract: Equal contributions AUTHOR CONTRIBUTIONZS conceived the study. GD identified the mouse phenotype and oversaw the human study. XL performed gene expression analysis, chemogenetic studies, and stereotaxic injections in mice. XH recruited human subjects and supervised human study. WZ performed histological studies and ChIP. YG coordinated the insulin clamp. WL made DNA constructs. SQ performed some of the mouse metabolic tests. JS performed gene expression analyses in human samples. JW, FL, JW, and CC collected h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 54 publications
3
29
0
Order By: Relevance
“…3F). This finding—that the central clock suffices for glucose homeostasis—complements recent work showing that it is necessary for glucose homeostasis ( 28 ). Together, these results underscore the importance of central processes in regulating glucose homeostasis and expands on the knowledge linking shift work to diabetes ( 29 ).…”
Section: Mainsupporting
confidence: 81%
“…3F). This finding—that the central clock suffices for glucose homeostasis—complements recent work showing that it is necessary for glucose homeostasis ( 28 ). Together, these results underscore the importance of central processes in regulating glucose homeostasis and expands on the knowledge linking shift work to diabetes ( 29 ).…”
Section: Mainsupporting
confidence: 81%
“…However, altered expression of these clock genes has been shown to induce changes in the glycometabolic profile. 17,19 We believe that growth hormone deficiency and the lack of nocturnal growth hormone surges alone are insufficient to explain insulin sensitivity in our case.…”
Section: Discussionmentioning
confidence: 69%
“…Ding et al have demonstrated differential expression of nuclear receptors in the suprachiasmatic nucleus which controls the diurnal rhythm of insulin sensitivity. 17 Similarly, the diurnal variation in free fatty acid availability governed by previous meals and diurnal expression of the PDK4 gene responsible for the availability of free fatty acids govern insulin sensitivity. 18 It is not known if cytotoxic chemotherapy and radiotherapy, which work by inducing DNA, can disrupt the intrinsic circadian rhythm leading to insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, targeted deletion of Bmal1 in neurons and glia was found to exacerbate neurodegenerative pathologies and behaviors, despite the retention of intact circadian behavioral and sleep–wake rhythms under LD conditions [ 101 ]. In line with these findings, a recent study showed that the nuclear receptors Rev-erbα/β in the GABAergic (γ-aminobutyric acid-producing) in neurons of the SCN (SCN GABA neurons) control the diurnal rhythm of insulin-mediated suppression of hepatic glucose production in mice, without affecting diurnal eating or locomotor behaviors during regular light–dark cycles [ 113 ]. These results suggest that the SCN central clock plays an important role in maintaining the internal synchrony of robust circadian programs in some peripheral clocks, while other peripheral clocks can be differentially modulated by light and feeding, regardless of the presence of a functional SCN central oscillator in the brain.…”
Section: The Role Of Brain Clocks In Circadian Rhythms and Disordersmentioning
confidence: 85%